Peran farmasis dalam meningkatkan kualitas pelayanan kesehatan - Rohmah, Evi Hidayatur (Maliki Interdisciplinary Journal, 2024)
Pharmacy is a field that focuses on the use of medicines and the management of other health products. In this article, we will discuss the important role of pharmacists in improving the quality of health care. In the health care system, pharmaceutical services are one of the core components playing a very important role, ranging from drug management, consultation with patients, monitoring drug side effects, and increasing public knowledge related to drug use.